Investment management (Vikas Publishing House, 2014)
This book has been written in a comprehensive manner, highlighting some of the important aspect of investment management. It aims at assisting the students to develop a through understanding of the concepts and theories underlying investment management in a systematic way. To accomplish this purpose, the recent thinking in the field of investment has been presented in a most lucid, simple and precise manner